Multispectral terahertz sensing with highly flexible ultrathin metamaterial absorber - Yahiaoui, Riad (2015)
We report the simulation, fabrication, and experimental characterization of a multichannel metamaterial absorber with the aim to be used as a label-free sensing platform in the terahertz regime. The topology of the investigated resonators deposited on a thin flexible polymer by means of optical lithography is capable of supporting multiple resonances over a broad frequency range due to the individual contribution of each sub-element of the unit cell. In order to explore the performance of the chosen structure in terms of sensing phenomenon, the reflection feature is monitored upon variation of the refractive index and the thickness of the analyte. We achieve numerically maximum frequency sensitivity of about 139.2 GHz/refractive index unit. Measurements carried out using terahertz time-domain spectroscopy show good agreement with the numerical predictions. The results are very promising, suggesting a potential use of the metamaterial absorber in wide variety of multispectral terahertz sensing applications.